How has gender income inequality in Ireland and the UK changed and why? - Silvia Avram; Karina Doorley; Claire Keane; Daria Popova (University of Essex, Centre for Microsimulation and Policy Analysis (CeMPA), 2025)
We examine the evolution of the gender income gap in UK and Ireland between 2008 and 2019 by income decile and decompose it to evaluate the relative importance of gender differences in working hours, self-employment, and hourly pay, as well as the redistributive effect of the tax-benefit system. We find that the biggest driver of the gender income gap in both countries is gender differences in employment/self-employment and working hours. These differences are especially large in the lower half of the income distribution, but their gradual reduction over the period we study led to a closing of the income gap in both countries. In contrast, the gender gap in hourly wages is more important in the middle and upper middle part of the income distribution, especially in the UK. The redistributive effect of the tax-benefit system by gender has fallen in the UK due to austerity measures but slightly increased in Ireland, primarily as a result of increased taxation. Further policy initiatives to align the employment rate and work hours of men and women in both countries could substantially reduce the gender gap in income in the future.
Keywords: J16; J31; 330; Gender inequality; Decomposition; Tax-benefit system; Ireland; United Kingdom